Sylvain Bemba, journalist and writer of the dream of a liberated Africa - (:unkn) unknown (My University, 2021)
Sylvain Bemba (1934-1995), a Congolese intellectual and man of letters, was one of the sub- Saharan writers who, from the end of the 1960s, used their literary writings to seek solutions to the ills of African populations in a neo-colonial crisis. Although highly esteemed by his compatriots and peers, who consider him a 'classic of literature in the Congo', and despite 'a strong and consistent work', he seems to have disappeared from the Francophone literary memory. Like many of his peers, Sylvain Bemba has been disadvantaged to the detriment of a handful of African writers who are better off because they have been "canonised". Above all, he has been a victim of the complex workings of the "World Republic of Letters". Based on historiographical and literary data, this study rehabilitates, (re)discovers and makes (re)discover this French-speaking author, his career as a committed African intellectual and his work. Relying on a corpus made up of the author's theatrical and novelistic texts published between the end of the 1960s and the beginning of the 1980s, the present work questions the cultural personality, the political thought and the scriptural esthetics of this sub-Saharan writer who is a lover of art and a supporter of human freedoms.
Keywords: African Research